Characterization of commercial natural rubber purified with transesterification - Thuong, Nghiem Thi; Nghia, Phan Trung; Kawahara, Seiichi (Vietnam Journal of Chemistry, 2016)
Highly purified commercial natural rubbers were prepared and characterized to elucidate the effect of processing condition on structure characteristic of the rubbers. In the present study, various commercial rubbers, i.e. Pale Crepe (PC), Ribbed Smoked Sheet (RSS3), Technically Specified Sheet (TSS8®), Standard Thailand Rubber (STR5L) and Standard Malaysian Rubber (SMR20) were purified by acetone extraction and transesterification (TE) to prepare highly purified commercial rubbers (TE-NR). The resulting TE-NRs were characterized by nuclear magnetic resonance (NMR) spectroscopy, Fourier transform infrared (FT-IR) spectroscopy and size exclusion chromatography (SEC). Epoxy group was found for PC, STR5L, RSS3, TSS8® and SMR20 and trans-1,4-isoprene unit from trans-1,4-isoprene units from cis-trans isomerization was found for TSS8® and SMR20 from the assignments of 1H-NMR signals. This result implies that the degradation, that is epoxidation and isomerization, took place during the processing of commercial rubbers. The damage of commercial natural rubbers was investigated with respect to its molecular weight. Keywords. Commercial rubber, transesterification, NMR, epoxidation, isomerization